Talent identification & development - Arnold, M. (2007)
Powerpoint-Präsentation zur aktuellen Situation im britischen Nachwuchsleistungssport (Schwerpunkt Leichtathletik)• Money does not buy success - 1994 - 1998 £600,000 p.a. - 2004 - 2008 £5million + p.a. • Other sports are now extremely active in recruitment and retention of participants • Good people count - Good people (coaches) = potential success - Retention of athletes - Conversion of athletes U20 -> PODIUM • Do not neglect Coach Education at all levels